Informação e inclusão: um estudo da aplicação de acessibilidade em portais legislativos estaduais - Alan Vasconcelos Alves (2012)
This work has the purpose to show a longitudinal picture of the web accessibility of the 27 state legislatures, take by the evaluation of each of them within one year, using an online tool called DaSilva. This tool evaluates the level of accessibility of the web pages, within a set of rules recommended by the Accessibility Model of Brazilian Electronic Government (e-MAG). In the case of the Legislative Assembly of Minas Gerais, a deeper case study was made, in which we compared the results obtained by both the automatic evaluation, as the empirical evaluation involving users with visual disabilities. This evaluation was performed on two occasions, also with a one-year period in which the site has undergone a complete overhaul. The empirical evaluation involved three users who were distinguished in degree of visual impairment and computer skills. Beyond the general picture, a structured interview was performed with the managers of the the sites. In this interview, the questions were related to technology, content management and accessibility policies. All data collected were organized in tables, charts and graphs. Concepts such as Accessibility, Universal Design and Usability are discussed and compared in order to clarify the boundaries and intersections in these three disciplines. In addition, web accessibility, especially in the government side, was placed as a primary field for Information Science to address and propose new theories and solutions.